Força de aperto de mão e estado nutricional de pacientes em hemodiálise - CAMPOS, Marta Isabel Valente Augusto Moraes (2012)
BACKGROUND: Protein energy wasting commonly occur in patients with chronic kidney disease. Changes in muscle function arise even before changes in anthropometric and biochemical parameters.Thus, a method for evaluating muscle function and strength becomes essential for these patients. OBJECTIVES: To evaluate the handgrip strength (HGS) and its association with nutritional status of patients with chronic kidney disease on hemodialysis. METHODS: A cross-sectional study conducted between May and July/2011. The sample included 90 patients, 48.8% male and 51.2% female. The HGS was performed three times with a hydraulic hand dynamometer (Takei) in the arm without fistula. For each patient were considered the best strength measure. Values lower than percentile 10 were considered as low HGS. The nutritional status diagnosis was given by Subjective Global Assessment (SGA). RESULTS: The average age was 52 ± 14.7 years. The hypertensive nephrosclerosis was the most frequent cause of chronic kidney disease (31.1%). The average HGS was among 32.0 ± 8.7kgf in men and 20.7 ± 6.1kgf in women (p<0.001). 11.3% of men and 21.7% of woman were classified as moderatey malnourished by SGA, 31.8% and 34.8% of men and women, respectively, were classified with low muscle function. Low HGS was associated with time on hemodialysis for men and showed good sensitivity (73.3%) and specificity (74.7%) for malnutrition diagnosis. In multiple logistic regression analysis, low-power handgrip strength prevalence was two times higher (PR =2.00, 95% CI: 1.19 to 3.34) for patients classified as moderate malnourished by SGA. CONCLUSION: This study showed high prevalence of low muscle function and good association between HGS and SGA in patients with chronic kidney disease on hemodialysis classified by dynamometry. It is suggested that HGS, an inexpensive and noninvasive measurement, can be used in clinical practice as a screening tool of nutritional status. It is sensitive for malnutrition diagnosis.